Física no futebol: objeto de aprendizagem gamificado para o ensino de física em mídias digitais por meio do esporte a partir do edutretenimento - De Grande, Fernando Chade [UNESP] (2016)
This study aims to present a proposal for a Learning Object using gamification to provide support to Science Education, specifically teaching classical mechanics. The dynamics of an action in football was used to illustrate concepts of Mechanical Physics, where students can interact with the Learning Object, interfering with physics variables and therefore changing the trajectory of the ball. The use of gamification implemented in the Learning Object through mechanics, aesthetics and game-thinking, has the intention to engage students, motivate and consequently promote the learning of Mechanical Physics. The simulation of reality produced in digital animation and distributed on digital media in the process of learning and teaching becomes a support in students’ cognitive development. The purpose of this work is to create an effective learning solution through edutertainment, associating concepts and formulas to students’ everyday life. Thus, approaching the teaching of science to student’s reality, is expected to form more critical and reflective citizens on social and ethical implications, where the importance of scientific work and technological aspects can contribute to improve the quality of life in society.